Liturgies of Empathy: Formation of Secular Spiritualities in the Fight against Gender-based Violence - Martínez-Moreno, Marco Julián (2025)
This article analyzes training workshops against gender-based violence in Brazil and Mexico as spaces that produce an inner-worldly secular spirituality, examining their rituals, processes of moral conversion, and the elaboration of a specific emotional interiority. The research is based on an ethnography that accompanied facilitators, activists, and professionals from the psychosocial and legal fields, using participant observation and discourse analysis. The findings reveal that these workshops function as secular rituals in which empathy is sacralized as a redeeming emotion, testimony enables the transformation from “victims” into “survivors,” and a moral dualism is established between “human agency” (good) and “oppressive structures” (evil). Furthermore, a structural symmetry is identified between the conversion logic of these spaces and the global expansion of Pentecostal and charismatic Christianities. The text concludes that the global expansion of human rights follows a religious logic of conversion, generating its own antagonist in a dialectical agonism with conservative actors, which redefines contemporary political-religious conflicts.